Encouraging Formal Invoicing and Reducing the VAT Impact on Low-Income individuals. (IMF Working Papers; Working Paper ;, 2021)
This paper analyses and compares two different groups of tools, the first to encourage the use of invoices (or payment systems) and the second to refund the VAT to low-income individuals. The analysis contributes to the existing literature by providing a clear characterization between these two groups of tools that are too often misunderstood and offers clear guidance to policymakers on the benefits and pitfalls of them based on available empirical studies and novel data analysis. Briefly, the first group includes a set of regressive and distortive tools (such as, allowing deducting the VAT paid on personal consumption from the PIT and reducing the VAT rate for using electronic means of payments or registration), while the second group includes tools that are less distortionary and improve income distribution (tax credits and VAT rate reduction targeted only at low-income individuals). This paper also finds that allowing the deduction of personal consumption against the PIT's taxable base (i) did not impact positively the VAT revenue in Guatemala and (ii) worsens the income distribution in Ecuador.